Developing a "Disaster Scenario" to prepare for the possibility of disruptions to maritime transportation serving coastal communities of Vancouver Island. (April 2023) - Islam, Samsul; Goerlandt, Floris; Sakalayen, Quazi Mohammed Habibus; Shi, Yangyan; Venkatesh, V.G.
Abstract: Planning for a crisis scenario that interferes with supply chain operations aims to speed up the recovery process. How to reduce disruptions in marine supply networks, especially in coastal communities, has not received adequate research. Therefore, in this research, a catastrophe scenario is created following consultations with a marine stakeholder and a marine geologist, and its viability is then evaluated by two maritime professionals. The scenario for the Fraser River is developed on the British Columbian island of Vancouver. The river's delta is susceptible to underwater landslides since it is composed of 65 % mud and clay and 35 % sand. Following an earthquake in Cascadia Subduction Zone, an underwater landslide may happen at low tide. This forecast makes sense since, as mentioned in earlier research, there is a strong likelihood that an earthquake of magnitude 9.0 with an epicentre location roughly 300 kilometres from Vancouver may occur. It is also anticipated that an underwater landslide with a retrogression toward the land of 450 m would take place according to the developed scenario of this research. Landslides in the Fraser River are likely to be at a location near to Sand Heads Lighthouse since large-scale earthquakes may trigger them. For example, the landslide developed in 1985 was around 100 m away from the Lighthouse. Thus, one of the main outcomes of the scenario is the destruction of the Sand Heads Lighthouse and the buoys from the outer delta. Additionally, the planned scenario may destroy structures along the coast, such as shipyards, quaysides, and other buildings. The Fraser River is mainly used by ferries and barges to bring foods from the mainland to Vancouver Island; as a result, the islanders place a great deal of reliance on this river to support their way of daily life. 90 % of their foods comes from outside the island, and there is only a three-day supply of fresh food in the shops. This signifies the importance of the Fraser River.